A band-limited receiver technology based on PAM4 modulation for the short distance optical transmission system - Qun LIU; Huiqin DU; Xianglin WU (Dianxin kexue)
In intensity modulation and direct detection of the short distance optical transmission system,there is some serious ISI (inter symbol interference) for the detected PAM4 signal due to the band-limited performance for the optical devices.A band-limited compensation algorithm based on DFE (decision feedback equalizer) combined FTN (fast than Nyquist) transmission was proposed.Then the algorithm performance gain was simulated in different band-limited scenarios,and the simulation results show that this algorithm can be useful to demodulate PAM4 receiver signal.What is more,there is about 1 dB performance gain at the bit error rate (BER) of 10-3for the serious conditions.